VLamax Correlates Strongly With Glycolytic Performance - Clark, Boris; Macdermid, Paul W (Research quarterly for exercise and sport, 2025)
V˙Lamax estimates an athlete's maximal-glycolytic rate. This study aimed to determine the relationships between the V˙Lamax and cycle ergometry efforts with a high-glycolytic energy contribution and the influence of V˙Lamax and VO2max on respiratory compensation point. Eleven national-international endurance cyclists (VO2max = 70.7 ± 5.9 ml·kg-1·min-1) completed a 15-s isokinetic-test with pre- and postlactate measurements to determine V˙Lamax, a 1-min maximal effort, and a ramp test to exhaustion in a single test session. The main findings showed strong relationships between V˙Lamax and the mean absolute (r = 0.83, p = .002) and relative (r = 0.88, p = .0004) power during the lactic interval of the 15-s isokinetic-test. This relationship weakened when comparing V˙Lamax with mean absolute (r = 0.52, p = .098) and relative (r = 0.29, p = .393) power during a 1-min maximal effort. Combining the V˙Lamax and V˙O2max data through multiple regression resulted in a positive effect on the estimation of respiratory compensation point. It was concluded that the V˙Lamax is a relevant indicator of maximal glycolytic rate. However, this metric currently lacks scientific validation as an accurate estimate of glycolytic rate and provides minimal extra information over using the power output from the isokinetic test alone. Practitioners may simply measure power over glycolytically demanding efforts to understand the maximal glycolytic rate of their athletes. V˙Lamax estimates an athlete's maximal-glycolytic rate. This study aimed to determine the relationships between the V˙Lamax and cycle ergometry efforts with a high-glycolytic energy contribution and the influence of V˙Lamax and VO2max on respiratory compensation point. Eleven national-international endurance cyclists (VO2max = 70.7 ± 5.9 ml·kg-1·min-1) completed a 15-s isokinetic-test with pre- and postlactate measurements to determine V˙Lamax, a 1-min maximal effort, and a ramp test to exhaustion in a single test session. The main findings showed strong relationships between V˙Lamax and the mean absolute (r = 0.83, p = .002) and relative (r = 0.88, p = .0004) power during the lactic interval of the 15-s isokinetic-test. This relationship weakened when comparing V˙Lamax with mean absolute (r = 0.52, p = .098) and relative (r = 0.29, p = .393) power during a 1-min maximal effort. Combining the V˙Lamax and V˙O2max data through multiple regression resulted in a positive effect on the estimation of respiratory compensation point. It was concluded that the V˙Lamax is a relevant indicator of maximal glycolytic rate. However, this metric currently lacks scientific validation as an accurate estimate of glycolytic rate and provides minimal extra information over using the power output from the isokinetic test alone. Practitioners may simply measure power over glycolytically demanding efforts to understand the maximal glycolytic rate of their athletes.